Generation of human induced pluripotent stem cell lines (iPSC) from adipose-derived mesenchymal stromal cells from two patients with systemic sclerosis - Mélanie Velier; Romain Appay; Robin Arcani; Romain Desprat; Stéphanie Simoncini; Anouck Zavarro; Danièle Noel; Lenha Bendaass; Christian Jorgensen; Quentin Gomes De Pinho; Audrey Benyamine; Brigitte Granel; et al. (Stem Cell Research)
Systemic sclerosis (SSc) is a rare and complex connective tissue disease associated with high morbidity and mortality. SSc is characterized by ischemic vasculopathy, cutaneous and visceral fibrosis and a dysimmune state (Denton and Khanna, 2017; Volkmann et al., 2023; Barnes and Mayes, 2012). We have derived induced pluripotent stem cell (iPSC) lines from two SSc patients aged 38 and 67 years with severe vascular phenotype. These iPSC lines expressed pluripotent markers, exhibited normal and stable genome, and differentiated into trilineage embryonic layers in teratoma formation assays. These SSc-specific iPSC lines can be differentiated into endothelial cells, providing a valuable model to elucidate vascular dysfunction and develop personalized therapeutic approaches.